Traffic as a Complex System: Four Challenges for Computer Science and Engineering - Bazzan, Ana L. C. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2007: Anais do XXXIV Seminário Integrado de Software e Hardware, 2007)
The increasing demand for mobility in our society poses challenges not only to traffic engineers and urban planning experts, but also to computer scientists, control engineers, and other researchers involved with information technology. There is no turnkey solution for the problem of traffic congestion in metropolitan areas, but several new tools and technologies are being developed to address the following challenges in traffic engineering: modeling and simulation of traffic systems; providing information to the users via travelers’ information systems; management of the system; and automation (of vehicles, highways, and intersections). These challenges are outlined here with the aim of proposing new research directions to computer scientists and electronic and computer engineers interested in the field of intelligent transportation systems.